The association of exposure to AIDS information and workplace with condom use among female commercial sex workers in Jakarta and Surabaya, Indonesia - Besral
This cross-sectional study estimated the prevalence of condom use and determined the association of workplace and exposure to AIDS information with condom use among female commercial sex workers in Jakarta and Surabaya, Indonesia. This study utilized secondary data from the 1998 Indonesia HIV/AIDS Behavioral Surveillance Survey (BSS).The prevalence of recent condom use among the study population was 36.7 percent (95CI=33.3 - 40.1 percent). The prevalence of condom use was higher (43) among women in the middle age compared to the younger (35) or the older (31) women. It was higher (40) among women with moderate or high education than women without any schooling or did not complete primary school (30). The prevalence of condom use was also higher among women who belong to the middle income (45) or high income (41) compared to low-income women (27).The results of multivariate logistic regression analysis showed that there was a significant association between exposure to AIDS information and condom use. Women who were exposed to AIDS information were more likely to have used condoms compared to women who did not get this kind of information. However, the association was modified by workplace and women's education. These associations were stronger among streets/fronts prostitutes than brothel-based prostitutes. Within the same workplace, these associations were stronger among low-educated women compared to moderately or highly educated women.This study also found a significant association between type of workplace and condom use. Women who work in brothels were more likely to have used condoms compared to women in prostitution fronts/streets. However, income and women's education modified the association. These associations were stronger among low- or high-educated women compared to women in the middle education. Within the same education, these associations were stronger among low-income women compared to moderate or high-income women.